OPTIMALISASI PROGRAM BRANDING DAN AKTIVASI MEREK DI ERA DIGITAL - Faif Yusuf (Universitas Bina Sarana Informatika, 2016)
In this digital era, business environment has its more challenges. Product innovation is not enough anymore. Marketing communication process may not be relevant regarding rapid changes in the dinamic environment. In order to maintain its corporate image dan company’s merekportfolio, company has to do something creative in all aspec of its public relation and branding activities. People have more choice than ever. They can get the products anywhere and can compare products and services down to the minute details. This requires a more intelligent manner of communication by companies.Brand activation is one of the important activities in the branding process. A successfull brand activation should have deep impact to consumer’s life to boost sales and corporate revenue. Key words : branding, brand activation, public relations